Current End-of-Life Care Needs and Care Practices in Acute Care Hospitals - Amy J. Thurston; Donna M. Wilson; Jessica A. Hewitt (Nursing Research and Practice)
A descriptive-comparative study was undertaken to examine current end-of-life care needs and practices in hospital. A chart review for all 1,018 persons who died from August 1, 2008 through July 31, 2009 in two full-service Canadian hospitals was conducted. Most decedents were elderly (73.8%) and urbanite (79.5%), and cancer was the most common diagnosis (36.2%). Only 13.8% had CPR performed at some point during this hospitalization and 8.8% had CPR immediately preceding death, with 87.5% having a DNR order and 30.8% providing an advance directive. Most (97.3%) had one or more life-sustaining technologies in use at the time of death. These figures indicate, when compared to those in a similar mid-1990s Canadian study, that impending death is more often openly recognized and addressed. Technologies continue to be routinely but controversially used. The increased rate of end-stage CPR from 2.9% to 8.8% could reflect a 1994+ shift of expected deaths out of hospital.